Exploring energy charging problem in swarm robotic systems using foraging simulation - Al Haek, Mohammed; Ismail , Amelia Ritahani; Ahmed Basalib, Ahmed Omar; Makarim, Nabiel (Universiti Teknologi Malaysia, 2015)
Swarm robotic systems is still a new field of study, and exploration of its applications and making use of its advantages can open the door for more research on this field in the near future. In swarm robotic systems, a number of simple robots can perform complex tasks efficiently than a single robot, giving robustness and flexibility to the group. However, robustness is one of the issues that need to be resolved as most of time the robots are suffering from low energy while performing the task. The main objectives of this paper are to highlight the robustness issue in swarm robotic systems and propose a solution to allow swarm robots to remain robust on achieving its task. To demonstrate the problem, foraging algorithm, which is inspired by ant’s behaviour, is simulated to highlight the problem of low energy in swarm robotic system and its effect on its robustness. One of the solutions is mainly by using power stations or banks, but both have its own limitation which are highlighted and discussed in this paper. Finally, the paper also explains on a potential mechanism, inspired by an immune system response, that will help swarm robots overcome the problem of low energy. Keywords: Swarm robotics, robustness, foraging, immune system response